The effects of hydrogen-induced lattice distortion and Nb-D formation on its permeation through niobium. (18th November 2021) - Liu, Qifa; Jin, Wei; Chen, Xiaohong; Mao, Xinchun; Liang, Chuanhui; Chen, Changan
Abstract: Abnormal permeation behavior of hydrogen through niobium has been investigated in this paper, i.e. the permeation flux saturated with long-term decrease after reaching a maximum. The diffusivity and permeability have been deduced from the decay edge of permeation transient. Three kinds of polycrystalline niobium foils with different annealing temperature have been compared, to verify the effect of defects and grain properties on the permeability and diffusivity. In the temperature range of (773–1023) K, the heat treatment along with the permeation cycles could either reduce or increase the permeability and diffusivity depending sensitively on temperature and showing a temperature threshold around 950 K. The permeation flux is proportional to square root of pressure, revealing that the abnormal permeation was still bulk diffusion-limited. The diffusivity gradually decreased with permeation cycles, and became more and more sensitive to pressure. The niobium foil expanded macroscopically along the gradient of hydrogen concentration, which reveals the strong and unrecoverable lattice distortion in this temperature and pressure range. The X-ray diffraction studies showed that splitting of all the Nb peaks and shifting of Nb-D peaks along with hydrogen loadings. The phase transition was expected to eliminate the lattice strain during hydrogen loading and which in turn acted as a diffusion barrier. Highlights: The abnormal permeation transient of hydrogen in Nb is systematically investigated. The abnormal permeation is bulk-diffusion controlled and pressure dependent. The temperature of annealing strongly affects the behavior of abnormal permeation. The reason for abnormal permeation is the formation of Nb-D due to phase transition.